Current consensus and controversy on the diagnosis of male lower urinary tract symptoms/benign prostatic hyperplasia - Cheng-Ling Lee; Hann-Chorng Kuo (Tzu Chi Medical Journal)
Traditionally, male lower urinary tract symptoms (LUTS) have been considered a synonym for benign prostate hyperplasia (BPH) because most male LUTS develops in aging men. Medical treatment should be the first-line treatment for BPH and surgical intervention should be performed when there are complications or LUTS refractory to medical treatment. Recent investigations have revealed that bladder dysfunction and bladder outlet dysfunction contribute equally to male LUTS. In the diagnosis of LUTS suggestive of BPH (LUTS/BPH), the following questions should be considered: Is there an obstruction? Are the LUTS caused by an enlarged prostate? What are the appropriate tools to diagnose an obstructive BPH? Should patients with LUTS be treated before bladder outlet obstruction is confirmed? This article discusses the current consensus and controversies in the diagnosis of LUTS/BPH.